Development of low-alloyed and rare-earth-free magnesium alloys having ultra-high strength. (1st May 2018) - Pan, Hucheng; Qin, Gaowu; Huang, Yunmiao; Ren, Yuping; Sha, Xuechao; Han, Xiaodong; Liu, Zhi-Quan; Li, Caifu; Wu, Xiaolei; Chen, Houwen; He, Cong; Chai, Linjiang; et al.
Abstract: Developing ultra-high strength in rare-earth-free Mg alloys using conventional extrusion process is a great challenge. What is even more difficult is to achieve such a goal at a lower processing cost. In this work, we report a novel low-alloyed Mg-2Sn-2Ca alloy (in wt. %) that exhibits tunable ultra-high tensile yield strength (360–440 MPa) depending on extrusion parameters. More importantly, there is little drop in mechanical properties of this alloy even when it is extruded at a speed several times higher than those used in the reported high strength Mg alloys. Examination of as-extruded microstructures of this Ca-containing Mg alloy reveals that the ultra-high strength is mainly associated with the presence of surprisingly submicron matrix grains (down to ∼0.32 μm). The results suggest that the Ca addition promotes accumulations of the pyramidal dislocations, which eventually transform into the low angular grain boundaries (LAGBs). The high number density of LAGBs separate the α-Mg matrix via either discontinuous dynamic recrystallization (DDRX) mechanism in the early stage or the continuous dynamic recrystallization (CDRX) mechanism in the later stage of extrusion, which effectively enhances the nucleation rates of the DRXed grains. More importantly, large amount of Ca segregation along LAGBs, accompanied with dynamically precipitated Mg2 Ca nano-phases, are detected in the present non-severely deformed samples. It is the combination of solute segregations and numerous Mg2 Ca nano-precipitates that contributes to the formation of the ultra-fine grains via pinning mechanism. The ultrafine grains size, Ca enrichment in most LAGBs, and residual Mg2 Ca nano-precipitates would in turn contribute significantly to the enhancement of the yield strength of the as-extruded Mg-2Sn-2Ca (wt.%) alloy. The low content of alloying elements and the fast one-step extrusion process render the present alloys low-cost and thus have great potential in large-scale industry applications. Graphical abstract: Image 1